ANALISIS MANAJEMEN PENYIARAN DI ERA TEKNOLOGI INFORMASI (KONVERGENSI MEDIA) - Hidayat, Riki (Konvergensi, 2015)
Today, competition is very crusial. First, in globalization era where like multinationalcompany can as developing to wider their operations. Including in Indonesia they also operatingand running their products, and then make local company as long as hopeless. Because of one ofthe basic what we have to increase are using Information Technology (IT) effectively. Ineconomy, information are assets in the company, to make effective and efficcient works. This era,many company not realized how many information has been processed and distributed well doneby using IT. Heading to globalization era, role of leaders as decision maker in organization willchange to information system with highly technology. Management process do not should beinterface and also not depend on certain groups, but throughout IT personally. Nowadays we areupdating with word society of information. Information society is named too as pasca-industrialsociety, means if information spread no one knows information but information society has beenformed. Information era also knowing by several component that involve in situation ofcommunication system. The component are information supplier, distribution system ofinformation, consumer information, and communication itself. Four of them are mutualconnected.Key Words : Global village, information technology, ecology media, management of broadcast,media convergence